Transfer printing method
By developing toner with electrostatic potential images containing specific resins and pigments, transferring the images to ordinary paper, and transferring the images to fabrics through hot pressing technology, the problem of image transfer instability in the prior art is solved, and high adhesion and durable image transfer effects are achieved.
Patent Information
- Application Number
- JP2023170001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
The prior art encounters difficulties in transferring images from paper media to fabrics, including thermal transfer paper or thermal transfer films requiring the use of release agents, and insufficient adhesion of toner to these media, resulting in unstable image transfer.
The electrostatic potential image development toner is used with amorphous polyester resin, crystalline polyester resin and pigments, the image is transferred to plain paper, and the image is transferred to fabric by hot pressing.
The formation of high adhesion and high durability images on paper is achieved, and the transfer efficiency and durability of images on fabrics is improved through hot press transfer technology.
Smart Images

Figure 2025059725000001 
Figure 2025059725000002 
Figure 2025059725000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a transfer printing method in which an image transferred and fixed on a paper substrate is transferred and fixed on a fabric. [Background technology]
[0002] With the advancement of technology in printers and copiers that use electrophotography, the scope of application of electrophotography has expanded from the conventional method of forming images only on paper to the formation of images on plastic films. On the other hand, direct image formation on fabric using electrophotography has not been easy because fabric is more flexible and thicker than paper, plastic films, etc. Therefore, in recent years, transfer printing methods in which an image formed on a transfer material is transferred onto fabric have been studied as a method of forming an image on fabric.
[0003] For example, Patent Document 1 describes a thermal transfer toner that is characterized by containing a charge control agent that contains a mixture of metal ions and metal complex ions, and a salt of an organic compound having a carboxy ion, and describes that by using the thermal transfer toner to transfer an original drawing copied onto a sheet to a receiving material, the fixability and durability of the drawing transferred onto a cloth are improved. Patent document 2 describes a transfer sheet having at least a transfer layer on a support, characterized in that a back layer containing a silicone compound that is solid at room temperature is provided on the side opposite the transfer layer, and it is described that this transfer sheet does not cause blocking when stored at high temperatures, prevents curling, and further improves transport stability within a copying device. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2000-321824 A [Patent Document 2] Japanese Patent Application Publication No. 11-70794 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the thermal transfer toner described in Patent Document 1 has the problem that an image cannot be transferred onto a fabric unless a thermal transfer paper or thermal transfer film coated with a release agent is used, and the toner has low fixability to the thermal transfer paper or thermal transfer film, and the transferred image has insufficient robustness. Also, the transfer sheet described in Patent Document 2 has the problem that the toner has low fixability to the transfer sheet when a toner image is formed on the transfer sheet. The present invention relates to a transfer printing method for solving these problems. [Means for solving the problem]
[0006] The present inventors have discovered that, in order to solve these problems, an image is transferred and fixed onto a paper substrate using a toner for developing an electrostatic latent image, which toner contains an amorphous polyester resin, a crystalline polyester resin, and a pigment, and the image is then transferred onto a fabric by contacting the paper substrate with the fabric, thereby solving the problems.
[0007] That is, the present invention provides the following [1]. [1] Step 1 of transferring and fixing an image formed using a toner for developing an electrostatic latent image containing an amorphous polyester resin, a crystalline polyester resin, and a pigment to a paper substrate; and Step 2 includes contacting and heating the image fixed on the paper substrate with a fabric to transfer and fix the image onto the fabric; Transfer printing method. Effect of the Invention
[0008] According to the present invention, a transfer printing method can be provided that can form an image with high fixability and fastness on a paper substrate, improve the transferability of the image from the paper substrate to a fabric, and form an image with high fastness when fixed on the fabric.
[0009] The detailed reasons why the transfer printing method of the present invention can form an image with high fixability and fastness on a paper substrate, improve the transferability of the image from the paper substrate to a fabric, and form an image with high fastness when fixed on the fabric are not clear, but are thought to be as follows. As in the thermal transfer paper or thermal transfer film described in Patent Document 1, a technique is known in which a transfer medium is used in which a release layer is provided on a paper substrate by silicone treatment or the like in order to improve the transferability of an image formed on the transfer medium to a fabric. However, since the release layer has low affinity with the toner forming the image, the fixability of the image formed on the transfer medium is low, and the formed image is easily detached from the transfer medium and / or damaged, which causes problems with image preservation. In addition, as in the transfer sheet described in Patent Document 2, a technique is known in which a transfer medium is used in which a release layer is provided on a paper substrate in order to improve the transferability of an image formed on the transfer medium to a fabric. However, there is also a problem with image preservation, in that the image formed on the transfer medium having a release layer is easily detached from the transfer medium and / or damaged. On the other hand, in the present invention, since general paper can be used as the paper substrate, it is considered that the fixability and robustness of the image fixed to the paper substrate are good, and such problems with image preservation hardly occur. An image formed on paper using a toner containing only a general amorphous resin as a binder resin cannot be easily removed because it is sufficiently fixed to the paper by the heat and pressure in the fixing process. Therefore, when the paper with the fixed image is brought into contact with the fabric and heat and pressure are applied, only a part of the toner near the surface of the image is transferred to the fabric, making it difficult to transfer the image from the paper to the fabric with high transferability. In contrast, the toner used in the transfer printing method of the present invention contains polyester resins such as amorphous polyester resins and crystalline polyester resins in the toner, and has high polarity due to the many ester groups, terminal hydroxyl groups, and carboxyl groups present in the polyester resins, and has high affinity for fabrics such as cotton and polyester. On the other hand, cellulose, the main component of the paper substrate, has high polarity, but since the paper substrate is given water resistance due to the effect of various paper additives such as sizing agents, it actually has a lower affinity with polyester than fabric. As a result, the image formed on the paper substrate is in a state where the toner is easily transferred to the fabric side to which the toner has a higher affinity, so it is thought that by applying heat while the image on the paper substrate and the fabric are in contact with each other, the image can be transferred to the fabric with high transferability. Furthermore, when the image is transferred from the paper substrate to the fabric, the toner-derived components forming the image on the paper substrate are instantly melted and reduced in viscosity by heating, and thus permeate the fabric quickly. Also, when pressure is applied in addition to heat, the components derived from the toner with reduced viscosity permeate deeper into the fabric and become entangled with the fibers constituting the fabric. The image fixed on the paper substrate is formed on the surface of the paper substrate because the fibers constituting the paper substrate are dense. In contrast, the fibers of the fabric are coarser than those of the paper substrate, so that the components derived from the toner permeate the fabric as described above, and most of the image is transferred to the fabric, and the image is fixed on the fabric by cooling. As a result, when the paper substrate is removed from the fabric, most of the image remains on the fabric, improving the transferability of the image on the paper substrate to the fabric and increasing the robustness of the image on the fabric. In addition, the toner of the present application uses a pigment as the coloring material instead of a dye, which is often used for dyeing fabrics. Pigments, unlike dyes, have very low solubility in water and therefore are superior in terms of durability, which is an issue with dyes, such as color transfer due to humidity, and are therefore thought to contribute to the high fastness of images on fabrics.
[0010] The definitions of various terms used in this specification are given below. The crystallinity of a resin is represented by the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter (DSC), i.e., the crystallinity index defined as "softening point (°C) / maximum endothermic peak temperature (°C)". The term "crystalline resin" refers to a resin having a crystallinity index of 0.6 or more and 1.4 or less. The term "amorphous resin" refers to a resin in which no endothermic peak is observed by differential scanning calorimetry (DSC), or, if an endothermic peak is observed, the resin has a crystallinity index of less than 0.6 or more than 1.4. The maximum endothermic peak temperature refers to the temperature of the endothermic peak with the largest peak area among the endothermic peaks observed under the conditions of the measurement method described in the Examples. The crystallinity of the resin can be adjusted by the types and ratios of the raw material monomers, and the production conditions (e.g., reaction temperature, reaction time, cooling rate), etc. The term "alkylene oxide adduct of bisphenol A" refers to the entire structure in which an alkylene oxide is added to 2,2-bis(4-hydroxyphenyl)propane. The term "carboxylic acid component" includes not only carboxylic acids but also their anhydrides and their alkyl esters having from 1 to 3 carbon atoms. In other words, when only the name of a carboxylic acid is mentioned in this specification, it is understood that the description also includes the anhydrides and alkyl esters of the carboxylic acid having from 1 to 3 carbon atoms. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Transfer printing method] The transfer printing method of the present invention comprises the steps of: A step 1 of transferring and fixing an image formed using a toner for developing an electrostatic latent image, the toner including an amorphous polyester resin, a crystalline polyester resin, and a pigment, onto a paper substrate; and The method includes step 2 of contacting and heating the image fixed on the paper substrate with a fabric to transfer and fix the image onto the fabric.
[0012] <Process 1> In step 1, an image formed using a toner for developing an electrostatic latent image, which contains an amorphous polyester resin, a crystalline polyester resin, and a pigment, is transferred and fixed onto a paper substrate. The toner for developing an electrostatic latent image and the paper substrate used in step 1, as well as the method for forming an image on the paper substrate, will be described in detail below.
[0013] [Toner for developing electrostatic latent images] The toner for developing electrostatic latent images (hereinafter, also simply referred to as "toner") used in the transfer printing method of the present invention contains an amorphous polyester resin and a crystalline polyester resin as binder resins, and a pigment.
[0014] <Amorphous polyester resin> The amorphous polyester resin as the binder resin of the toner contains a polycondensate of an alcohol component and a carboxylic acid component. There is no particular limitation as long as it contains a polycondensate of an alcohol component and a carboxylic acid component, and examples thereof include a polyester resin made of a polycondensate and a modified polyester resin. Examples of modified polyester resins include a composite resin containing a polyester resin segment and an addition polymerization resin segment, a urethane modified polyester resin, and an epoxy modified polyester resin. Among these, an amorphous polyester resin that is a polycondensate of an alcohol component containing a diol and a carboxylic acid component containing an aromatic dicarboxylic acid is preferable.
[0015] (Alcohol content) Examples of the alcohol component include alkylene oxide adducts of aromatic diols, aliphatic diols, alicyclic diols, and trihydric or higher polyhydric alcohols. Among these, alkylene oxide adducts of aromatic diols are preferred from the viewpoints of improving the transferability of an image from a paper substrate to a fabric and improving the fastness of an image fixed on the fabric.
[0016] The alkylene oxide adduct of an aromatic diol is preferably an alkylene oxide adduct of bisphenol A, and more preferably an alkylene oxide adduct of bisphenol A represented by the following general formula (I).
[0017] [ka]
[0018] In general formula (I), OR 1 and R 2 O is an oxyalkylene group, and R 1 and R 2 each independently represents an ethylene group or a propylene group, x and y represent the average number of moles of alkylene oxide added and are each a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 4 or less. Examples of the alkylene oxide adduct of bisphenol A include a propylene oxide adduct of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] and an ethylene oxide adduct of bisphenol A. These may be used alone or in combination. Among these, the propylene oxide adduct of bisphenol A and the ethylene oxide adduct of bisphenol A are preferred.
[0019] Examples of the aliphatic diol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2,2-dimethyl-1,3-propanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol. Examples of the alicyclic diol include hydrogenated bisphenol A and cyclohexanedimethanol. Examples of the trihydric or higher polyhydric alcohol include glycerin, pentaerythritol, trimethylolpropane, sorbitol, and sorbitan.
[0020] The content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 60 mol % or more, more preferably 80 mol % or more, even more preferably 90 mol % or more, still more preferably 95 mol % or more, and preferably 100 mol % or less, from the viewpoints of improving the transferability of the image from the paper substrate to the fabric and improving the fastness of the image fixed on the fabric.
[0021] (Carboxylic acid component) Examples of the carboxylic acid component include dicarboxylic acids and polyvalent carboxylic acids having three or more carboxylic acids. Examples of the dicarboxylic acid include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Examples of aromatic dicarboxylic acids include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred. The aliphatic dicarboxylic acid preferably has 2 or more, more preferably 3 or more, and preferably has 30 or less, more preferably 20 or less. Examples of the aliphatic dicarboxylic acid include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, azelaic acid, and succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms. Examples of the succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among these, succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms is preferred, and dodecenylsuccinic acid is more preferred. The trivalent or higher polyvalent carboxylic acid is preferably a trivalent carboxylic acid, for example, trimellitic acid, preferably trimellitic acid or its anhydride.
[0022] The total content of aromatic dicarboxylic acids in the carboxylic acid component is preferably 60 mol % or more, more preferably 70 mol % or more, and preferably 100 mol % or less, from the viewpoints of improving the transferability of an image from a paper substrate to a fabric and improving the fastness of an image fixed on the fabric.
[0023] When the carboxylic acid component contains an aliphatic dicarboxylic acid, the content of the aliphatic dicarboxylic acid is preferably 1 mol % or more, more preferably 3 mol % or more, and preferably 30 mol % or less, more preferably 15 mol % or less, from the viewpoints of improving the transferability of the image from the paper base material to the fabric and improving the fastness of the image fixed on the fabric.
[0024] When the carboxylic acid component contains a trivalent or higher polyvalent carboxylic acid, the content of the trivalent or higher polyvalent carboxylic acid is, from the viewpoint of improving the transferability of the image from the paper base material to the fabric and improving the fastness of the image fixed on the fabric, preferably 3 mol % or more, more preferably 5 mol % or more, even more preferably 10 mol % or more, still more preferably 15 mol % or more, and is preferably 35 mol % or less, more preferably 30 mol % or less, and even more preferably 25 mol % or less.
[0025] The equivalent ratio (COOH group / OH group) of the carboxy group (COOH group) of the carboxylic acid component to the hydroxy group (OH group) of the alcohol component constituting the amorphous polyester resin is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0026] (Method for producing amorphous polyester resin) The amorphous polyester resin may be produced, for example, by a method of polycondensing an alcohol component and a carboxylic acid component.
[0027] The polycondensation of an alcohol component and a carboxylic acid component can be carried out, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere at a temperature of 120° C. or higher and 250° C. or lower, using an esterification catalyst, an esterification promoter, and a radical polymerization inhibitor described below as necessary.
[0028] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) di(2-ethylhexanoate), and titanium compounds such as titanium diisopropoxybis(triethanolaminate). Examples of the esterification promoter that can be used together with the esterification catalyst include gallic acid. The amount of the esterification catalyst used is preferably 0.01 parts by mass or more and 10 parts by mass or less based on 100 parts by mass in total of the alcohol component and the carboxylic acid component. The amount of the esterification promoter used is preferably 0.001 part by mass or more and 1 part by mass or less based on 100 parts by mass in total of the alcohol component and the carboxylic acid component. Furthermore, examples of the polymerization inhibitor include radical polymerization inhibitors such as 4-tert-butylcatechol. When a polymerization inhibitor is used, the amount of the polymerization inhibitor used is preferably 0.001 part by mass or more and 1 part by mass or less based on 100 parts by mass in total of the alcohol component and the carboxylic acid component.
[0029] (Physical properties of amorphous polyester resin) The softening point of the amorphous polyester resin is preferably 90°C or higher, more preferably 95°C or higher, and even more preferably 100°C or higher, and is preferably 150°C or lower, more preferably 140°C or lower, and even more preferably 130°C or lower. The glass transition temperature of the amorphous polyester resin is preferably 50° C. or higher, more preferably 55° C. or higher, and preferably 80° C. or lower, more preferably 75° C. or lower, and further preferably 70° C. or lower. The acid value of the amorphous polyester resin is preferably 1 mgKOH / g or more, more preferably 2 mgKOH / g or more, and preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, and further preferably 25 mgKOH / g or less.
[0030] The amorphous polyester resins may be used alone or in combination of two or more. The softening point, glass transition temperature, and acid value of the amorphous polyester resin can be appropriately adjusted by the types and amounts of raw material monomers used, as well as production conditions such as reaction temperature, reaction time, and cooling rate, and these values can be determined by the methods described in the examples. When two or more kinds of amorphous polyester resins are used in combination, the softening point, glass transition temperature and acid value of the mixture are preferably within the above-mentioned ranges.
[0031] In the present invention, the amorphous polyester resin is preferably substantially water-insoluble. Here, "substantially water-insoluble" means that when the amorphous polyester resin is vacuum dried at 40°C for 12 hours and reaches a constant weight, and is dissolved in 100 g of water at 25°C until it is saturated, the amount of dissolution is 1 g or less. When the amorphous polyester resin contains an acid group, the amount of dissolution is the amount of dissolution when the acid group of the amorphous polyester resin is neutralized by 100 mol % with sodium hydroxide.
[0032] <Crystalline polyester resin> The crystalline polyester resin used as the binder resin of the toner is, for example, a crystalline polyester resin which is a polycondensation product of an alcohol component and a carboxylic acid component.
[0033] (Alcohol content) The alcohol component is preferably an α,ω-aliphatic diol. The carbon number of the α,ω-aliphatic diol is preferably 2 or more, more preferably 4 or more, and even more preferably 6 or more, and is preferably 16 or less, more preferably 14 or less, and even more preferably 12 or less. Examples of α,ω-aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol. Among these, ethylene glycol, 1,6-hexanediol, and 1,12-dodecanediol are preferred.
[0034] The alcohol component may contain other alcohol components different from the α,ω-aliphatic diol. Examples of the other alcohol components include aliphatic diols other than α,ω-aliphatic diols, such as 1,2-propanediol and neopentyl glycol; aromatic diols, such as alkylene oxide adducts of bisphenol A; and trihydric or higher alcohols, such as glycerin, pentaerythritol, and trimethylolpropane. These alcohol components may be used alone or in combination.
[0035] (Carboxylic acid component) The carboxylic acid component is preferably an aliphatic dicarboxylic acid. The carbon number of the aliphatic dicarboxylic acid is preferably 4 or more, more preferably 8 or more, and is preferably 14 or less, more preferably 12 or less. Examples of the aliphatic dicarboxylic acid include fumaric acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid. Among these, sebacic acid and dodecanedioic acid are preferred. These carboxylic acid components may be used alone or in combination.
[0036] The carboxylic acid component may contain other carboxylic acid components different from the aliphatic dicarboxylic acid. Examples of other carboxylic acid components include aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid, and polyvalent carboxylic acids having three or more carboxylic acids. These carboxylic acid components may be used alone or in combination.
[0037] The content of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, still more preferably 95 mol% or more, and preferably 100 mol% or less, still more preferably 100 mol%.
[0038] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0039] (Method for producing crystalline polyester resin) The crystalline polyester resin can be produced, for example, by the same method as that for the amorphous polyester resin described above.
[0040] (Physical properties of crystalline polyester resin) The softening point of the crystalline polyester resin is preferably 60°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher, and is preferably 120°C or lower, more preferably 110°C or lower, and even more preferably 100°C or lower. The melting point of the crystalline polyester resin is preferably 60° C. or higher, more preferably 65° C. or higher, and is preferably 110° C. or lower, more preferably 100° C. or lower, and further preferably 90° C. or lower. The acid value of the crystalline polyester resin is preferably 5 mgKOH / g or more, more preferably 8 mgKOH / g or more, even more preferably 10 mgKOH / g or more, and is preferably 35 mgKOH / g or less, more preferably 30 mgKOH / g or less, even more preferably 25 mgKOH / g or less.
[0041] The crystalline polyester resin may be used alone or in combination of two or more. The softening point, melting point, and acid value of the crystalline polyester resin can be appropriately adjusted by the type and amount of raw material monomer used, as well as production conditions such as reaction temperature, reaction time, and cooling rate, and these values can be determined by the method described in the examples. When two or more kinds of crystalline polyester resins are used in combination, it is preferable that the softening point, melting point and acid value of the mixture are each within the above-mentioned ranges.
[0042] In the present invention, the crystalline polyester resin is preferably substantially water-insoluble. Here, the term "substantially water-insoluble" has the same definition as that of the amorphous polyester resin.
[0043] The mass ratio of the amorphous polyester resin to the crystalline polyester resin in the toner [amorphous polyester resin / crystalline polyester resin] is preferably 70 / 30 or more, more preferably 80 / 20 or more, even more preferably 90 / 10 or more, and is preferably 99 / 1 or less, more preferably 98 / 2 or less.
[0044] [Pigment] The toner used in the transfer printing method of the present invention contains a pigment as a colorant. As the pigment, a known pigment used for toners can be used. For example, carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, and disazo yellow can be used. The toner may be either a black toner or a color toner other than black. The content of the pigment is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 20 parts by mass or less, more preferably 10 parts by mass or less, relative to 100 parts by mass of the binder resin, from the viewpoints of improving the transferability of the image from the paper base material to the fabric and improving the fastness of the image fixed on the fabric.
[0045] The toner used in the transfer printing method of the present invention may contain additives such as a release agent, a charge control agent, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, and a cleaning property improver, in addition to the amorphous polyester resin, the crystalline polyester resin, and the pigment.
[0046] (Release agent) Examples of the release agent include hydrocarbon waxes such as polypropylene wax, polyethylene wax, polypropylene-polyethylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more.
[0047] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, and is preferably 110° C. or lower, more preferably 95° C. or lower.
[0048] The content of the release agent is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 1.5 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 7 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0049] (Charge control agent) The charge control agent is not particularly limited, and may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent.
[0050] Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", and "Bontron N-11" (all manufactured by Orient Chemical Industry Co., Ltd.); triphenylmethane dyes containing tertiary amines as side chains, quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industry Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX VP435" (manufactured by Clariant); polyamine resins such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives such as "PLZ-2001" and "PLZ-8001" (all manufactured by Shikoku Chemical Industry Co., Ltd.); and styrene-acrylic resins such as "FCA-701PT" (manufactured by Fujikura Chemical Industry Co., Ltd.).
[0051] Examples of the negatively chargeable charge control agent include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizen Spiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (both manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; quaternary ammonium salts such as "COPY CHARGE NX VP434" (manufactured by Clariant), nitroimidazole derivatives, and organometallic compounds.
[0052] The content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 5 parts by mass or less, more preferably 2 parts by mass or less, based on 100 parts by mass of the binder resin.
[0053] <Toner manufacturing method> The toner used in the transfer printing method of the present invention may be a toner obtained by any of the known methods such as the melt kneading method, the emulsion phase inversion method, the polymerization method, etc., but from the viewpoint of productivity and pigment dispersibility, a pulverized toner by the melt kneading method is preferred. In the case of a pulverized toner by the melt kneading method, raw materials such as a release agent and a charge control agent are mixed uniformly in a mixer such as a Henschel mixer as necessary, and then melt kneaded in an internal kneader, a single-screw or twin-screw extruder, an open roll type kneader, etc., and cooled, pulverized, and classified to produce the toner.
[0054] The volume median particle size (D 50 ) is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less. 50 ) refers to the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size. In addition, when the toner is treated with an external additive, the volume median particle size of the toner particles before treatment with the external additive is regarded as the volume median particle size of the toner.
[0055] (External additives) In the toner used in the transfer printing method of the present invention, in order to improve the transferability when forming an image on a paper substrate in step 1, an external additive is preferably used. Examples of the external additive include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, zinc oxide, etc., and organic fine particles such as resin particles such as melamine-based resin fine particles and polytetrafluoroethylene resin fine particles, and two or more kinds may be used in combination. Among these, silica is preferred, and hydrophobic silica that has been subjected to a hydrophobic treatment is more preferred.
[0056] Examples of hydrophobic treatment agents for hydrophobizing the surfaces of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), silicone oil, octyltriethoxysilane (OTES), and methyltriethoxysilane.
[0057] The average particle size of the external additive is preferably 10 nm or more, more preferably 15 nm or more, and preferably 250 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less, and even more preferably 90 nm or less.
[0058] The content of the external additive is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner before being treated with the external additive, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less.
[0059] [Method of forming an image on a paper substrate] As a method for forming an image on a paper substrate, a known image forming method using an electrophotographic image forming apparatus can be used. For example, a method of forming an image on a paper substrate using an image forming apparatus including an image carrier, a developing unit that develops an electrostatic latent image formed on the image carrier with toner to form a toner image, a transfer unit that transfers the toner image on the image carrier to paper, and a fixing unit that fixes the toner image transferred to the paper substrate can be used.
[0060] [Paper base material] As the paper substrate, various known printing papers can be used. Examples of various printing papers include uncoated printing paper, lightly coated printing paper, coated printing paper, special printing paper, and information paper, and more specifically, high-grade printing paper, medium-grade printing paper, gravure paper, art paper, coated paper, wood-free paper, color wood-free paper, and PPC paper. In addition to printing paper, paper substrates that can be printed by an electrophotographic image forming device and on which a toner image can be sufficiently fixed can be used, such as packaging paper, industrial paper, and the like, and specifically, pure white roll paper, bleached kraft paper, and unbleached kraft paper. Among them, from the viewpoint of forming an image with high fixability and robustness on the paper substrate, paper substrates selected from high-grade printing paper, medium-grade printing paper, gravure paper, art paper, coated paper, wood-free paper, color wood-free paper, PPC paper, pure white roll paper, bleached kraft paper, and unbleached kraft paper are preferred.
[0061] <Process 2> In step 2, the image formed on the paper substrate in step 1 is brought into contact with a fabric and heated to transfer and fix the image onto the fabric. The fabric used in step 2 and the method of transferring and fixing the image onto the fabric are described in detail below.
[0062] [Fabric] As the fabric, any woven fabric using known natural fibers or chemical fibers can be used. Examples of natural fibers include cotton, hemp, silk, etc., and examples of chemical fibers include polyester, polyurethane, nylon, rayon, etc. Among them, from the viewpoint of improving the transferability of an image from a paper substrate to the fabric and improving the fastness of the image fixed on the fabric, a fabric made of cotton or polyester is preferred.
[0063] [Method of transferring and fixing an image onto a fabric] The image is transferred and fixed onto the fabric by contacting the image fixed on the paper substrate with the fabric. In order to improve the transferability of the image from the paper substrate to the fabric and the fastness of the image fixed onto the fabric, it is preferable to further apply pressure, and it is more preferable to apply heat and pressure simultaneously.
[0064] Examples of devices that can be used to apply heat and pressure in step 2 include a known flat press machine and a roll press machine. Flat auto press (HP-54N, HP-84N), flat sublimation press (HSP-126FA, HSP-1010, HSP-1310, HSP2210, HSP-5400), manufactured by Hashima Co., Ltd. Sublimation press machine (AFP-700TP, AFP-800TP, etc.), manufactured by Itsumi Co., Ltd. Hot press tabletop CYPT (CYPT-10, CYPT-20, CYPT-30, CYPT-50), manufactured by Shinto Kogyo Co., Ltd. - Tabletop test press (SA-302, SA-303), high-precision hot press machine (SA-401, SA-501), manufactured by Tester Sangyo Co., Ltd. etc. Roll press machines include continuous sublimation transfer presses (HSP-1300RL, HSP-1600RL, HSP-2000RL), all of which are manufactured by Hashima Corporation. When a roll press machine is used, the linear speed (feed speed, machine speed) is preferably 1 m / min or more, more preferably 1.5 m / min or more, and even more preferably 2 m / min or more, from the viewpoint of improving the transferability of the image from the paper base material to the fabric and improving the fastness of the image fixed on the fabric, and from the viewpoint of productivity, it is preferably 7 m / min or less, more preferably 5 m / min or less, and even more preferably 3 m / min or less.
[0065] In step 2, the heating temperature is preferably 60° C. or higher, more preferably 80° C. or higher, and even more preferably 100° C. or higher from the viewpoint of improving the transferability of the image from the paper substrate to the fabric and improving the fastness of the image fixed on the fabric, and is preferably 200° C. or lower, more preferably 180° C. or lower, and even more preferably 160° C. or lower from the viewpoint of productivity. In this case, the paper substrate and the fabric are heated to the same temperature as the heating temperature. When pressure is applied in step 2, the pressure applied is preferably 0.1 MPa or more, more preferably 0.5 MPa or more, even more preferably 1 MPa or more, from the viewpoints of improving the transferability of the image from the paper substrate to the fabric and improving the fastness of the image fixed on the fabric, and is preferably 5 MPa or less, more preferably 4 MPa or less, even more preferably 3 MPa or less. The time for applying heat and pressure is preferably 10 seconds or more, more preferably 30 seconds or more, and even more preferably 50 seconds or more, from the viewpoint of improving the transferability of the image from the paper substrate to the fabric and improving the fastness of the image fixed on the fabric, and is preferably 300 seconds or less, more preferably 200 seconds or less, and even more preferably 100 seconds or less, from the viewpoint of productivity.
[0066] In step 2, the paper substrate is removed after the image is transferred onto the fabric. Any method may be used to remove the paper substrate as long as it does not adversely affect the image on the fabric, and examples of the method include a method of peeling the paper substrate from the fabric to which the image has been transferred, and a method of removing the paper substrate by washing the fabric to which the image has been transferred together with the paper substrate with water. EXAMPLES
[0067] The present invention will be described in more detail below with reference to examples, etc. In the following examples, the various physical properties were measured by the following methods.
[0068] [Measurement method] The properties of the resin and toner were measured and evaluated by the following methods.
[0069] [Softening points of resin and toner] Using a flow tester "CFT-500EX" (Shimadzu Corporation), 1 g of the sample was heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point.
[0070] [Resin Crystallinity Index] Using a differential scanning calorimeter "Q-20" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample was weighed into an aluminum pan and cooled to 0°C at a rate of 10°C / min. The sample was then left to stand for 1 minute, after which it was heated to 180°C at a rate of 10°C / min and the calorific value was measured. The temperature of the peak with the largest peak area among the observed endothermic peaks was taken as the maximum endothermic peak temperature, and the crystallinity index was calculated by (softening point (°C)) / (maximum endothermic peak temperature (°C)).
[0071] [Glass transition temperature and melting point of resin and glass transition temperature of toner] Using a differential scanning calorimeter "Q-20" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled to 0°C at a rate of 10°C / min to prepare a sample for measurement. The temperature was then increased at a rate of 10°C / min to measure the amount of heat. The peak temperature with the largest peak area among the observed endothermic peaks was taken as the maximum endothermic peak temperature. In the case of a crystalline resin, the peak temperature was taken as the melting point. In the case of an amorphous resin, the temperature at the intersection of the extension line of the baseline below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the apex of the peak was taken as the glass transition temperature.
[0072] [Acid value of resin] The measurement was performed in accordance with JIS K0070, except that the measurement solvent was a mixed solvent of acetone and toluene [acetone:toluene=1:1 (volume ratio)].
[0073] [Volume Median Particle Size of Toner] Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion: Polyoxyethylene lauryl ether "EMULGEN (registered trademark) 109P" (manufactured by Kao Corporation, HLB (hydrophile-lipophile balance) = 13.6) was dissolved in the electrolyte to obtain a dispersion with a concentration of 5 mass %. Dispersion conditions: 10 mg of a measurement sample of dried toner particles was added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser. Thereafter, 25 mL of electrolyte was added, and the mixture was further dispersed for 1 minute using an ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles could be measured in 20 seconds. Then, 30,000 particles were measured, and the volume median particle size (D 50 ) was sought.
[0074] [Production of resin] Production Example A1 (Production of Amorphous Polyester Resin A-1) The inside of a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 1456g of propylene oxide (2.2) adduct of bisphenol A, 4057g of ethylene oxide (2.2) adduct of bisphenol A, 2487g of terephthalic acid, 40g of tin (II) di(2-ethylhexanoate), and 1.6g of gallic acid were added, and the mixture was heated to 235°C under a nitrogen atmosphere while stirring and maintained for 6 hours. The pressure in the flask was then further reduced and maintained at 8.3kPa until the softening point reached the temperature shown in Table 1, to obtain amorphous polyester resin A-1. Various physical properties of the resin are shown in Table 1.
[0075] Production Example A2 (Production of Amorphous Polyester Resin A-2) The inside of a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 3433g of propylene oxide (2.2) adduct of bisphenol A, 2125g of ethylene oxide (2.2) adduct of bisphenol A, 1624g of terephthalic acid, 209g of dodecenylsuccinic anhydride, 40g of tin (II) di(2-ethylhexanoate), and 1.6g of gallic acid were added, and the mixture was heated to 235°C under a nitrogen atmosphere while stirring, and after maintaining for 8 hours, the pressure in the flask was further reduced and maintained at 8.3kPa for 1 hour. After that, the mixture was returned to atmospheric pressure, cooled to 210°C, 626g of trimellitic anhydride was added, and after maintaining for 1 hour at 210°C, the pressure in the flask was further reduced and maintained at 8.3kPa, and the reaction was continued until the softening point reached the temperature shown in Table 1, to obtain amorphous polyester resin A-2. Various physical properties of the resin are shown in Table 1.
[0076] [Table 1]
[0077] Production Example C1 (Production of Crystalline Polyester Resin C-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 2860g of 1,6-hexanediol and 5140g of sebacic acid were added. The temperature was raised to 135°C while stirring, and after holding at 135°C for 3 hours, the temperature was raised from 135°C to 200°C over 10 hours. Then, 32g of tin(II) di(2-ethylhexanoate) was added, and the mixture was held at 200°C for another 1 hour. The pressure in the flask was then reduced, and the reaction was continued at 8.3kPa until the acid value reached the value shown in Table 2, to obtain crystalline polyester resin C-1. Various physical properties of the resin are shown in Table 2.
[0078] Production Example C2 (Production of Crystalline Polyester Resin C-2) The inside of a 10 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, 1699 g of ethylene glycol and 6301 g of dodecanedioic acid were added, and the same operation as in Production Example C1 was carried out to obtain crystalline polyester resin C-2. Various physical properties of the resin are shown in Table 2.
[0079] Production Example C3 (Production of Crystalline Polyester Resin C-3) The inside of a 10 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, 4020 g of 1,12-dodecanediol and 3980 g of sebacic acid were placed in, and the same operation as in Production Example C1 was carried out to obtain crystalline polyester resin C-3. Various physical properties of the resin are shown in Table 2.
[0080] [Table 2]
[0081] [Toner Production] Manufacturing Example X1 (Manufacturing of Toner X1) 100 parts by mass of the binder resin shown in Table 3, 5 parts by mass of the pigment "ECB-301" (manufactured by Dainichiseika Chemical Industry Co., Ltd., Phthalocyanine Blue (PB15:3)), 3 parts by mass of the release agent "Carnauba Wax C1" (manufactured by Kato Yoko Co., Ltd., melting point: 83°C), and 0.5 parts by mass of the charge control agent "Bontron E-304" (manufactured by Orient Chemical Industry Co., Ltd.) were mixed in a Henschel mixer. The obtained mixture was melt-kneaded at a screw rotation speed of 200 r / min and a barrel set temperature of 100°C using a co-rotating twin-screw extruder with a kneading section total length of 1560 mm, a screw diameter of 42 mm, and a barrel inner diameter of 43 mm, to obtain a molten kneaded product. The feed rate of the mixture was 20 kg / h, and the average residence time was about 18 seconds. The obtained molten kneaded product was cooled and coarsely crushed, then crushed in a jet mill, and classified using an airflow classifier (manufactured by Nippon Pneumatic Mfg. Co., Ltd.) to obtain a volume median particle size (D 50 ) yielded 7.0 μm toner particles. 100 parts by mass of the obtained toner particles and 1.0 part by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) as external additives were mixed in a Henschel mixer (manufactured by Nippon Coke Co., Ltd.) at a rotation speed of 3000 r / min (circumferential speed: 32 m / sec) for 3 minutes to obtain toner X1. The physical properties of toner X1 are shown in Table 3.
[0082] Production Examples X2 to X6 and Production Example Y1 (Production of Toners X2 to X6 and Y1) Toners X2 to X6 and Y1 were obtained in the same manner as in Production Example X1, except that the binder resin and pigment were changed to the types and / or parts by mass shown in Table 3. The physical properties of toners X2 to X6 and Y1 are shown in Table 3.
[0083] [Table 3]
[0084] Examples 1 to 6 and Comparative Example 1 Toners X1 to X6 and Y1 were mounted on a color printer "MICROLINE 5400" (manufactured by Oki Electric Industry Co., Ltd.), and the toner adhesion amount was 0.4 to 0.5 mg / cm 2 A solid image measuring 2.5 cm wide x 2.5 cm long was output (transferred) without being fixed to the paper substrate so that the image would look like this. Next, a printer of the same model, but with a temperature-variable fixing unit, was prepared, and the image was fixed at a fixing unit temperature of 150°C at a speed of 1.4 seconds per sheet in portrait orientation for A4 size paper, and then cooled to room temperature, thereby fixing the toner image onto the paper substrate. The paper substrate was a high-quality paper "S Kinbishi (basis weight 105 g / m 2 ) (manufactured by Mitsubishi Paper Mills Co., Ltd.) was processed offline using a supercalender device. The fixability of the image formed on the paper substrate and the robustness of the image on the paper substrate were evaluated using the methods described below. Next, the paper substrate with the fixed image was placed on top of a polyester cloth (100% polyester, plain white, satin fabric) so that the image was in contact with the cloth, and heat and pressure were applied for 60 seconds at a temperature of 120°C and a pressure of 2MPa using a tabletop test press SA-302 (manufactured by Tester Sangyo Co., Ltd.). The paper substrate and the cloth were removed from the press while still in contact with each other, and cooled to room temperature. The paper substrate was then peeled off from the cloth to obtain a cloth with the image transferred thereto. The transferability of the image to the cloth and the robustness of the image transferred to the cloth were evaluated by the method described below.
[0085] [Evaluation method] [Image fixation on paper substrate] For images on a paper substrate, a high-quality paper "Excellent White Paper" (manufactured by Oki Electric Industry Co., Ltd.) was placed under the paper substrate on which the image was printed, and the "density of the image before tape application" was measured using a spectrophotometer X-Rite eXact (manufactured by X-Rite). Next, a mending tape called "Scotch (registered trademark) Mending Tape 810" (manufactured by 3M Ltd., width 18 mm) was applied to the image, and then a 500 g cylindrical weight (contact area: 157 mm 2) was placed on the image and pressed back and forth once. The attached tape was then peeled off, and the "image density at the area where the tape was peeled off" was measured in the same manner as above for the area where the tape was peeled off. The fixation rate was calculated from the measured image density using the following formula. The higher the fixation rate, the better the image fixation. The results are shown in Table 4. Fixation rate = "Image density where tape is removed" ÷ "Image density before tape is applied" x 100
[0086] [Robustness of images on paper substrate] The fastness of the image formed on the paper substrate before being transferred to the fabric was evaluated in accordance with JIS L 0849:2013 (test method for dye fastness to friction). The paper substrate with the image fixed thereon was attached to a Gakushin-type friction tester (Daiei Scientific Instruments Manufacturing Co., Ltd.), and the image was rubbed back and forth 100 times with a 200g load using a friction element with a cotton cloth attached. The cotton cloth was removed from the friction element and the degree of coloring was judged to determine the fastness value. The higher the fastness grade, the better the fastness. The results are shown in Table 4.
[0087] [Image transfer onto fabric] For the image on the paper substrate before transferring the image to the fabric, a high-quality paper "Excellent White Paper" (manufactured by Oki Electric Industry Co., Ltd.) was placed under the paper substrate on which the image was printed, and the "density of the image on the paper substrate before transfer" was measured using a spectrophotometer X-Rite eXact (manufactured by X-Rite). Next, the "density of the image transferred onto the fabric" was measured for the image on the fabric after transfer in the same manner as above. The transfer rate was calculated from the measured image density using the following formula. The higher the transfer rate, the better the transferability of the image onto the fabric. The results are shown in Table 4. Transfer rate = "Density of the image on the transferred fabric" ÷ "Density of the image on the paper substrate before transfer" x 100
[0088] [Image robustness on fabric] The fastness of the image on the fabric was evaluated in the same manner as for the evaluation of the fastness of the image on the paper substrate, and the results are shown in Table 4.
[0089] Example 7 An image was transferred onto cotton cloth in the same manner as in Example 1, except that cotton cloth (100% cotton, white, plain) was used instead of the polyester cloth. Evaluations were carried out in the same manner as in Example 1. The results are shown in Table 4.
[0090] Reference example 1 An image was transferred onto polyester fabric in the same manner as in Example 1, except that FOREVER's "CLASSIC" transfer paper for laser printer fabrics having a release layer was used as the paper substrate. Evaluation was performed in the same manner as in Example 1. The results are shown in Table 4.
[0091] [Table 4]
[0092] From Table 4, it was found that the images formed on the paper substrate using the toners X1 to X6 had high fixation rate and fastness on the paper substrate, and the transfer rate of the images from the paper substrate to the polyester cloth and cotton cloth was also high. Furthermore, the images transferred onto the polyester cloth or cotton cloth had excellent fastness. On the other hand, the image formed on the paper substrate using toner Y1 not containing crystalline polyester resin had a lower fixation rate on the paper substrate than the images formed using toners X1 to X6, and the transfer rate of the image from the paper substrate to the polyester cloth was also lower. Furthermore, the image transferred onto the polyester cloth had low fastness. Moreover, it is believed that an image formed on a general transfer paper using toner X1 has a low fixation rate and is poor in storage stability.
Claims
1. A step 1 of transferring and fixing an image formed using a toner for developing an electrostatic latent image, the toner including an amorphous polyester resin, a crystalline polyester resin, and a pigment, onto a paper substrate; Step 2 includes contacting and heating the image fixed on the paper substrate with a fabric to transfer and fix the image onto the fabric; Transfer printing method.
2. 2. The transfer printing method according to claim 1, wherein a mass ratio of the amorphous polyester resin to the crystalline polyester resin in the toner (amorphous polyester resin / crystalline polyester resin) is from 70 / 30 to 99 / 1.
3. The transfer printing method according to claim 1 or 2, wherein the melting point of the crystalline polyester resin is 60° C. or higher and 110° C. or lower.
4. The transfer printing method according to any one of claims 1 to 3, wherein the step 2 is carried out by applying heat at 50°C to 200°C and a pressure at 0.1 MPa to 5 MPa.
5. The transfer printing method according to any one of claims 1 to 4, wherein the paper base material is selected from high-grade printing paper, medium-grade printing paper, gravure paper, art paper, coated paper, fine paper, colored fine paper, PPC paper, pure white roll paper, bleached kraft paper, and unbleached kraft paper.
6. The transfer printing method according to any one of claims 1 to 5, wherein the fabric is made of at least one type of fiber selected from the group consisting of cotton, linen, silk, polyester, polyurethane, nylon, and rayon.
Citation Information
Patent Citations
Transfer sheet and image forming method using the same
JP1999070794A
Toner for heat transfer and transfer method
JP2000321824A